A Consistent Cross-Border Seismic Hazard Methodology for Loss Estimation and Risk Management along the Border Regions of Canada and the United States. Issue 1 (February 2015) - Thenhaus, Paul C.; Campbell, Kenneth W.; Gupta, Nitin; Smith, David F.; Khater, Mahmoud M.
We provide a methodology that seamlessly integrates national seismic hazard models across the Canada-U.S. border to provide earthquake risk managers with updated and consistent seismic hazard science and technology in the two countries. Consistent with our U.S. hazard model, we developed a new Canadian model that incorporates (1) spatially varying seismicity for the major metropolitan areas of southeastern and southwestern Canada and the United States, (2) a comprehensive probabilistic model for the Cascadia subduction zone that includesM 8.0–9.2 interface earthquakes, (3) a consistent set of ground motion prediction equations across eastern and western North America, and (4) a soil-based attenuation (SBA) methodology that mitigates uncertainty in the conversion of earthquake motions from rock to soil, on which the majority of exposure is located. NEHRP site conditions are mapped for all of Canada from existing geological data, and NEHRP site factors are used to account for local site conditions.